Metode Kritik Alkitab Julius Wellhausen - Reni Triposa; Demsy Jura (Sekolah Tinggi Teologi SAPPI Ciranjang, 2024)
The Wellhausen Document Hypothesis is a theory that suggests the Pentateuch (Genesis, Exodus, Leviticus, Numbers, and Deuteronomy) was composed from four main sources, namely the Jahwist (J), Elohist (E), Priestly (P), and Deuteronomic (D) sources. This theory was first proposed by Julius Wellhausen in the 19th century and has become one of the most influential theories in the study of the Bible. According to this hypothesis, J is the oldest source, dating from the early monarchy period (around the 10th century BCE). J refers to God as Yahweh and focuses on the relationship between God and the people of Israel. E is a more recent source, originating from the northern monarchy period (around the 9th century BCE). E refers to God as Elohim and emphasizes the moral and ethical aspects of the relationship between God and humans.